Dampak faktor ekonomi dan kebijakan perdagangan terhadap ekspor Indonesia di 10 negara tujuan utama - Fahrudin, Moris; Purnomo, Didit (Journal of Economics Research and Policy Studies, 2025)
This study analyzes the factors that influence Indonesia’s exports to 10 destination countries, namely China, USA, Japan, India, Malaysia, Singapore, Philippines, Rep. Korea, Vietnam, and the Netherlands, during 2018-2022 using a panel data regression model. The variables used are the number of workforce, digital economy, per capita income, and foreign investment as independent variables. At the same time, total exports are the dependent variable. The results of the analysis show that the Fixed Effect Model (FEM) is the best, where per capita income, foreign investment, and exchange rates do not have a significant effect on exports. This study found that the workforce and digital economy positively affect Indonesia’s exports. Countries with a skilled workforce and the application of digital technology encourage increased exports through increased productivity and operational efficiency. The existence of Indonesian economic policies that emphasize the development of workforce quality and the adoption of digital technology can provide insights that can be realized in activities. Implications provide insight into creating digital infrastructure from various parties that can collaborate to create a digital infrastructure for exports.